2016
DOI: 10.1007/s00431-016-2709-7
|View full text |Cite
|
Sign up to set email alerts
|

Are adolescents with high self-esteem protected from psychosomatic symptomatology?

Abstract: • Despite being free of serious physical illness, many adolescents often report subjective health complaints, such as psychosomatic symptoms • As children in this life stage develop independence and autonomy, new types of social relationships, and identity, their social needs and skills also change What is new: • Need to belong, shyness, and competitiveness may serve as social behavioral risk factors for adolescents' psychosomatic symptomatology, whereas self-esteem may play a protective role • The role of soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 42 publications
2
19
0
1
Order By: Relevance
“…However, a limitation is that the reliability of the need to belong (.61) and relationship satisfaction (.63) scales was moderate at best. This was lower than in studies measuring belongingness needs in adult samples (Hartung & Renner, ; Leary et al, ; Mellor et al, ; Pickett, Gardner, & Knowles, ), though similar to another study of adolescents (Piko et al, ). A comparison of correlations between a study of adults (Mellor et al, ) and our study led us to believe that our sample is not divergent from other (older) samples.…”
Section: Strengths and Limitationssupporting
confidence: 41%
See 1 more Smart Citation
“…However, a limitation is that the reliability of the need to belong (.61) and relationship satisfaction (.63) scales was moderate at best. This was lower than in studies measuring belongingness needs in adult samples (Hartung & Renner, ; Leary et al, ; Mellor et al, ; Pickett, Gardner, & Knowles, ), though similar to another study of adolescents (Piko et al, ). A comparison of correlations between a study of adults (Mellor et al, ) and our study led us to believe that our sample is not divergent from other (older) samples.…”
Section: Strengths and Limitationssupporting
confidence: 41%
“…Previous work has established various negative effects of social isolation on health (for a meta‐analysis, see Holt‐Lunstad et al, ). There is also evidence linking high need for social connection to various physical and psychosomatic health complaints (Hartung & Renner, ; Mellor, Stokes, Firth, Hayashi, & Cummins, ; Piko, Varga, & Mellor, ). The interplay between social network quality and need for social connection has, however, not received as much attention.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, researchers have been increasingly pointing out a link between self-es-teem and the mental and physical aspects of adolescent health (Byrne, 2000;Erol & Orth, 2011;Piko, Varga, & Mellor, 2016). Erol and Orth (2011) found a positive relationship between self-esteem and physical health in adolescence, where adolescents with higher self-esteem showed better health.…”
Section: Subjective Health Complaints Interparentalmentioning
confidence: 99%
“…In particular, it has been shown that the higher the self-esteem, the lower the number of somatic complaints such as abdominal (stomach) pain and malaise (Robinson, Mitchell, Kirkeby, & Meier, 2006) and depression and anxiety (Byrne, 2000;De Jong, Sportel, De Hullu, & Nauta, 2012). According to Piko et al (2016), self-esteem has been found to provide protection against stress and it is related to lower levels of psychosomatic symptoms and mental health problems in both sexes.…”
Section: Subjective Health Complaints Interparentalmentioning
confidence: 99%
“…However, it is negatively associated with binge drinking (Piko et al, 2016). Moreover, shy adolescents are less likely to present an alcohol use disorder (Burstein, Ameli-Grillon, & Merikangas, 2011).…”
Section: Introductionmentioning
confidence: 99%